Impact of Crack Length into Pipe Conveying Fluid Utilizing Fast Fourier transform Computer Algorithm - Radhwan Hussein Abdulzhraa AL-Sagheer; K. I. Mohammed; Alaa Abdul Hussein Mezher; Karrar Abdullah Mohammed Habeeban (Institute of Advanced Engineering and Science, 2019)
One of the most prominent problems experienced by the oil facilities is leakage of oil from the pipes. This problem caused 55% of oil refineries to be shut off. Oil leakage is a common problem that often results in oil waste, damage, and hazard to public health. Therefore, it is necessary to use Modern technologies to reduce this phenomenon and avoid them in advance. Pipes that convey fluids have many uses in various industries and living facilities. Risk increases when the fluid inside the pipe is flammable. In this work, main case that cause damage to the pipe, longitudinal crack is investigate.This work presents a new experimental model based on computer applications with a Fast Fourier transform (FFT) algorithm for testing the effect of longitudinal crack length by frequency and ultrasonic measurements to measure fluid velocity. The method is used for plastic pipe with 2 cm internal diameter, 3 cm external diameter, and 1 m length. The modulus of elasticity of the material is 800 N/mm2 according to the ISO 178 test method. The pipe conveys oil with simply supported ends. The results show that FFT model shows better features compared with other ways that depends on visual inspection or localized measurements which gave an external perception of pipeline damage. FFT model offers a reliable and cheap style for ensuring pipeline integrity and warning the risks before its occurrence. From the observations made the fundamental natural frequency (FNF) decreases by increasing of crack length in the pipe that conveys fluid